Czech legislation approaching several and joint liability for VAT payment - Tomáš Sejkora (Prawo Budżetowe Państwa i Samorządu, 2019)
This article is devoted to the implementation of Article 205 of the VAT directive in the Czech Republic. It focuses on the basic aspects of this instrument tackling VAT evasion from the EU law perspective, a description of the relevant Czech legislation and finally, its comparison with the EU law standards. The content of this article points out that Czech public law bodies do not respect the barriers for several and joint liability for VAT payment settled by the CJEU, moreover that the Czech Parliament failed to implement the right instrument when it implemented the personal guarantee for VAT payment. It is obvious that the complex approach to the implementation is missing in this case and the Czech transposition of the several and joint liability for VAT payment broadly failed to comply with the EU level of VAT regulation. The scientific methods used are description, analysis, induction and deduction.